2018
DOI: 10.1016/j.acvd.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in children participating in a non-selective INR self-monitoring VKA-education programme

Abstract: This QoL study provides original data from a large cohort of children and their parents participating in a formalized INR self-monitoring education programme for VKA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 31 publications
4
33
0
Order By: Relevance
“…Nevertheless, more than two thirds of fathers participated in this study and their mean level of anxiety reached nearly 7 out of 10. In the current era, fathers of children with a CHD have been increasingly involved in their child's health condition, and they accurately evaluate their child's quality of life, as we recently reported . In the literature, more attention has been given to father reports in psychosocial studies.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Nevertheless, more than two thirds of fathers participated in this study and their mean level of anxiety reached nearly 7 out of 10. In the current era, fathers of children with a CHD have been increasingly involved in their child's health condition, and they accurately evaluate their child's quality of life, as we recently reported . In the literature, more attention has been given to father reports in psychosocial studies.…”
Section: Discussionmentioning
confidence: 88%
“…A recent review of more than 30 articles noticed the impact of a cardiac surgery on the parental mood after prenatal diagnosis and this even far after the birth . When focusing on the parents' perspective, we recently found that the parental assessment of the child well‐being was more pejorative than the child self‐reported well‐being, with relevant differences between fathers' and mothers' assessments . However, we did not evaluate the level of parental anxiety.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the continuity of our clinical research program on QoL in patients with CHD [6,14,[30][31][32]34], we expect to observe an improvement of QoL in patients undergoing the transition education program. Patientreported outcomes (PRO) have been increasingly used in clinical research [35], therefore, using QoL as a primary outcome in the TRANSITION-CHD trial seems particularly adapted to such a therapeutic education program.…”
Section: Discussionmentioning
confidence: 97%
“…2.8 Sample size The primary outcome is the change in the self-reported QoL score with the PedsQL instrument. In our previous QoL cross-sectional studies in patients with CHD [14,30,31] as well as in similar studies using patient related outcomes, a difference of less than 5 points seems irrelevant and a difference of more than 10 points is ideal, but rarely obtained in clinical trials [32,33]. Therefore, we hypothesized to observe an increase in the overall QoL score of 7 ± 13.5 points (over 100).…”
Section: Methodsmentioning
confidence: 93%